Moodle for beginners - Hillar, Silvina P.; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"Moodle is one of the most popular open source platforms to create, manage, and organize content for courses. This course shows you how to create both activities and resources, creating them in a Moodle course and also using external tools. We'll enhance our Moodle course by creating external websites, blogs, videos, and channels in order to create a dynamic course. Furthermore, you'll learn to work with repositories and e-portfolios and organize the content to gamify the course. You'll learn how to deal with and organize information, edit, and share it. By the end of this course, you will be up and running with Moodle, having made your repositories portable for collaborative work."--Resource description page.
Presenter, Silvina Paola Hillar.
Title from title screen (viewed May 19, 2017).
Date of publication from resource description page.
Keywords: Moodle; Computer-assisted instruction -- Computer programs; Instructional systems -- Design; Web sites -- Authoring programs; Electronic books